Habitat, emosie en "n eko-teologiese verstaan van menswees: In gesprek met Johan Buitendag - Veldsman, Daniël P. (HTS teologiese studies, 2014)
Habitat, emotion and an eco-theological understanding of humanity: In conversation with Johan Buitendag. The question on what his viewpoint of an eco-theological understanding of life entails is firstly posed in conversation with the South African systematic theologian Johan Buitendag. His standpoint, in which he argues for the constitutive significance of habitat against the background of the philosophical, biological and theological contours of descriptions of what life is, is set forth. He suggests that human life should be described with regard to habitat in its constitutive significance and subsequently in regard to a value system, and concludes that human life as homo religiosus must be understood from an eco-theological viewpoint as ontologically extended (‘ontologies uitgebreid’). His eco-theological viewpoint is secondly taken up in an explication of the sense making of human life by humans, determined and shaped by their biological roots in their habitat. Lastly the affective-cognitive dimension of being human with specific emphasis on affectivity is expounded as representing the embodiment of the logic of survival of personhood in their habitat.